Editorial - Hayes, Grahame (PINS-Psychology in Society, 2026)
In this issue we continue some of the psychoanalytic discussion which we started in our focus on psychoanalysis in Psychology in society 14 (1990). Leonard Bloom presents a challenging re-assertion of what he considers to be the four main basic insights of Freud. These are (1) the unconscious, (2) sexuality and the libido, (3) repression, and (4) transference processes. Readers might want to take issue with what exactly constitutes the "basic insights" of Freud's work, but what seems incontrovertible is Bloom's argument about the revisionism of much of contemporary psychoanalysis. Bloom also criticises the dampening of Freud's radicality by neo behavioural perspectives in psychology. He tries to reclaim Freud's centrality as a thinker about human experience and the value of human life in his application of Freud's work to a consideration of questions of racism and freedom. Bloom presents us with an account of Freud as a humanist thinker concerned with social dilemmas.